A Network of Community Partners Representing Multiple Communities: Developing a Tool for Matching Community-Engaged Scholars with Community Partners - Rebecca L. Foco; Frank Fox; Cornelia Ramsey; Elizabeth B. D. Ripley (The University of Alabama, 2022)
The Community Partnership for Ethical Research (CPER) was a multi-faceted research project designed to test a model of community engagement using a network of community partners called Community Advocates for Research (CARs). The goals of the project included developing systems to sustain and expand the CARs network. This article presents one facet of this project-a method of effectively and efficiently managing data about the CARs. User-friendly surveys and a database were designed for the management of these data. The web-based survey allows data capture in the community. Moreover, the web-based database tools facilitate centralized data collection and management that will contribute to the sustainability of the network of CARs beyond the initial grant that provided the funding for its development. This article describes the surveys and database and their utility for other institutions desiring to establish similar networks of community partners.